2022
DOI: 10.3390/ijerph191912501
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Concurrent Stunting and Obesity among Children under 2 Years from Socio-Economically Disadvantaged Backgrounds in the Era of the Integrated Nutrition Programme in South Africa

Abstract: In view of persistent stunting and increasing rates of obesity coexisting among children in the era of the Integrated Nutrition Programme, a cross-sectional study was conducted to determined concurrent stunting and obesity (CSO) and related factors using a random sample of child–mother pairs (n = 400) in Mbombela, South Africa. Sociodemographic data was collected using a validated questionnaire, and stunting (≥2SD) and obesity (>3SD) were assessed through respective length-for-age (LAZ) and body mass index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 74 publications
1
17
1
Order By: Relevance
“…high in energy-dense food, low in nutrient-dense food) (Popkin et al, 2012). It is suggested that low consumption of animal protein inhibits linear growth, whereas a high-carbohydrate diet may increase fat deposition (Modjadji et al, 2022).…”
Section: Minimum Dietary Diversity 123 Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…high in energy-dense food, low in nutrient-dense food) (Popkin et al, 2012). It is suggested that low consumption of animal protein inhibits linear growth, whereas a high-carbohydrate diet may increase fat deposition (Modjadji et al, 2022).…”
Section: Minimum Dietary Diversity 123 Discussionmentioning
confidence: 99%
“…high in energy-dense food, low in nutrient-dense food) (Popkin et al , 2012). It is suggested that low consumption of animal protein inhibits linear growth, whereas a high-carbohydrate diet may increase fat deposition (Modjadji et al , 2022). In fact, the food cost can be a barrier to implementing a lower energy and nutrient-dense diet for poorer households (Darmon and Drewnowski, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the most recent malnutrition estimates, the 2023 Joint Child Malnutrition Estimates produced by the UNICEF, WHO, World Bank collaboration, notes that most of the children who were diagnosed with malnutrition in 2022 lived in Africa and Asia, with two out five children under five experiencing stunting coming from Africa (UNICEF / WHO and The World Bank Group, 2023). Evidence from sub-Saharan African country contexts such as Ghana, Ethiopia, and South Africa shows that children who experience a combination of stunted growth and overweight, otherwise known as concurrent stunting and overweight or the “double burden” of malnutrition, face higher risks of obesity and chronic lifestyle diseases such as diabetes and hypertension in adulthood (Atsu et al, 2017; Farah et al, 2021; Modjadji et al, 2022), once again underscoring the long-term health impacts of childhood malnutrition. Additionally, women who were stunted as children are more likely to give birth to low-weight babies, who, in turn, face a higher risk of childhood illnesses such as pneumonia, diarrhoea, and malnutrition (Khatun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of economic and demographic transition, stunting remains one of the persistent concerns with alarming rates of overweight and obesity in South Africa [ 29 , 30 , 31 , 32 , 33 , 34 ], giving rise to a double burden of malnutrition [ 35 , 36 ]. This rationalized use of a convergent parallel mixed methods design allows to best understand the magnitude of malnutrition through multilevel influences in a rural area.…”
Section: Introductionmentioning
confidence: 99%